The bequest tax as long-term care insurance - Johann K. Brunner (Johannes Kepler University of Linz, Department of Economics, 2012)
I study a model of a representative individual who has a motive for leaving bequests and is at risk of needing long-term care in old age. I assume - as is typical for OECD countries - that the individual is not fully insured against this risk. Moreover, at realization the individual is unable to adapt labor supply or consumption; then expenditures for long-term care result in a one-to-one reduction of the estate. In this situation a tax on bequests provides insurance and its introduction causes a smaller deadweight loss than an income or consumption tax. I also characterize the optimal tax and transfer system in this model.
Keywords: H21; H24; I13; 330; estate tax; long-term care insurance; Erbschaftsteuer; Optimale Besteuerung; Pflegeversicherung; Erbe; Theorie